Model Pembelajaran Kooperatif Tipe Numbering Head Together (NHT) Dengan Media Foto untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Ips Ekonomi (Pendidikan Ekonomi, 2013)
The  model  of  this  research  used  classroom  action  research  (CAR).  The  results  showed  (1)  The learning outcomes of students in the first cycle to obtain the value of classical completeness was 69.44%,  while  the  second  cycle  obtained  by  classical  completeness  was  88.88%,  and  the  third cycle obtained  by  classical  completeness  was  97.22%.  (2) Activities of  teachers  in  implementing cooperative learning model type with the media photos Number Head Together in 1st, 2nd and 3rd cycle  performed  in  good  criteria.  (3)  Activities  of  students  during  cooperative  learning  Number Head Together media types are classified on the criteria of good photos. (4) The response of students to the type of cooperative learning Number Head Together media photos showed that students were motivated to participate in learning IPS Economy (5) All obstacles which appear in Cooperative Learning Number Head Together types with media images can be resolved.Key Words: Number Head Together,  Photo, learning outcomes.